Front Cover: Linear Multiselenium Interactions in Dicationic Oligomers of 1, 5‐(Diselena)canes: Behavior of Semc σ(mcc‐nee) (6≤mc≤16) Elucidated with QTAIM Dual Functional Analysis (ChemistryOpen 7/2021). Issue 7 (1st July 2021) - Hayashi, Satoko; Nishide, Taro; Nagata, Kengo; Nakanishi, Waro
Abstract : The Front Cover shows the key message of our work, that is, the covalency of the chalcogen bonds, in an elegantly simple and attractive manner. To that end, the chalcogen bonds are represented by schematic 3D structures of the bond donor D2 Ch and the bond acceptor A ‐, and their attractive interaction in green. Then, a colorful molecular orbital (MO) diagram where the HOMO‐LUMO mixing is represented by the mixing of red (HOMO) and blue (LUMO) into purple (MO) is represented. More information can be found in the Full Paper by Satoko Hayashi et al. .